RESEARCH ON SEISMIC APPLICATION FOR GAS HYDRATE EXPLORATION IN TU CHINH - VUNG MAY AREA - Huong, Phan Thien; Tung, Nguyen Thanh; Hanh, Bui Thi (Vietnam Journal of Marine Science and Technology, 2016)
There is a little doubt that global resources of conventional hydrocarbon such as oil, gas, coal are on the decline that naturally leads to the search for new source of energy. Gas hydrate is considered as one of the potential candidates and has been of interest all over the world in the last decade. In Vietnam the interest in gas hyrate is recently growing quickly with one major government project being implemented, however there is not yet a dedicated survey for gas hydrate exploration so far. The search for gas hydrate, therefore, needs to employ the conventional seismic data acquired for petroleum exploration. In this paper, the authors attempt to point out initial indications of gas hydrate offshore Vietnam by analyzing seismic data.